2022
DOI: 10.1111/rssa.12800
|View full text |Cite
|
Sign up to set email alerts
|

Power Law in COVID-19 Cases in China

Abstract: The novel coronavirus (COVID‐19) was first identified in China in December 2019. Within a short period of time, the infectious disease has spread far and wide. This study focuses on the distribution of COVID‐19 confirmed cases in China—the original epicentre of the outbreak. We show that the upper tail of COVID‐19 cases in Chinese cities is well described by a power law distribution, with exponent around one in the early phases of the outbreak (when the number of cases was growing rapidly) and less than one th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…As power law/memory effect in disease transmission is directly related to some forced COVID-19 control measures like lockdown, social distancing, use of face-mask, therefore, using these measures may control future waves in these locations. These findings agree with some recent results of the power law effect on COVID-19 incidence growth pattern [8] , [13] , [77] , [78] , [79] . Therefore, government and policymakers may focus on restricting and to restrict the forthcoming waves in these four locations (see Figs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As power law/memory effect in disease transmission is directly related to some forced COVID-19 control measures like lockdown, social distancing, use of face-mask, therefore, using these measures may control future waves in these locations. These findings agree with some recent results of the power law effect on COVID-19 incidence growth pattern [8] , [13] , [77] , [78] , [79] . Therefore, government and policymakers may focus on restricting and to restrict the forthcoming waves in these four locations (see Figs.…”
Section: Discussionsupporting
confidence: 93%
“…By analyzing COVID-19 incidence data from different countries around the globe, several studies concluded that at the beginning of the epidemic, data trends followed some exponential growth, and as the epidemic progress over the years, data trended to exhibit a power law growth pattern [8] , [9] , [10] , [11] , [13] , [77] , [78] , [79] . In general, power law growth in COVID-19 cases is directly related to control measures, in the sense that the less strict the control, the smaller the power law exponent, and hence the slower the disease progresses to its end [8] , [13] , [77] , [77] , [78] , [79] . Thus, it is reasonable to assume that the COVID-19 transmission process follows some power law [79] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some papers studying the distribution of caseloads for COVID-19 during the early phases of the pandemic ( Beare & Toda, 2020 ; Blasius, 2020 ; Chan et al, 2021 ; Komarova et al, 2020 ; Singer, 2020 ; Vazquez, 2020 ). Beare and Toda (2020) ; Blasius (2020) ; Komarova et al (2020) ; Singer (2020) ; Vazquez (2020) ; Ahundjanov et al (2022) have found some evidence of a power-law distribution in the number of COVID-19 cases. Chan et al (2021) found a negative binomial was the best fitting count regression model to COVID-19 case counts.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally [ 34 ], proposed a new zero-state coupled Markov switching negative binomial model in which the disease alternates between periods of presence and absence in each area using a series of partially hidden nonhomogeneous Markov chains coupled between nearby locations. The distribution of COVID-19 confirmed cases in China was examined by [ 35 ] With respect to the dynamics of Power law.…”
Section: Introductionmentioning
confidence: 99%